The Role of Islamic Economics and Finance in the Era of Digital Transformation, Sustainable Growth and Geopolitical Uncertainty - Perry Warjiyo (Journal of Islamic Monetary Economics and Finance, 2026)
This paper is based on a keynote speech delivered at The 11th International Islamic Monetary Economics and Finance Conference (11th IIMEFC). As a keynote contribution, this article does not include a formal abstract.